Acculturation, Dietary Behaviors, and Macronutrient Intake Among Mexican Americans With Prediabetes: The Starr County Diabetes Prevention Initiative. Issue 1 (February 2023) - Brown, Sharon A.; Becker, Heather A.; García, Alexandra A.; Velasquez, Mary M.; Tanaka, Hirofumi; Winter, Mary A.; Perkison, William B.; Brown, Eric L.; Aguilar, David; Hanis, Craig L.
Purpose: The purpose of the study was to examine the influences of sex and acculturation on dietary behaviors, macronutrient intake, and dietary quality in participants enrolled in a diabetes prevention initiative in Starr County, Texas. Methods: Baseline data from the Starr County diabetes prevention study (N = 300) were analyzed—acculturation (country of origin, years in Starr County, language and food preferences), depressive symptoms (Patient Health Questionnaire-9), healthy eating self-efficacy (Weight Efficacy Lifestyle Questionnaire-Short Form), diet quality (USDA Healthy Eating Index), fat avoidance (Fat Avoidance Scale, Spanish version), and macronutrients. Descriptive statistics and univariate analysis of covariance were used to examine differences based on acculturation, controlling for sex. Results: Participants were predominantly female (73%) and, on average, 51 years of age. Language and food preferences favored Spanish language and Hispanic foods, respectively. The majority (71%) was born in Mexico but had resided in Starr County for 33 years, on average. Depressive symptoms were moderate, and eating self-efficacy scores suggested low confidence in making healthy food choices, particularly for saturated fats. Spanish language preference was associated with worse dietary habits. The mean dietary quality score was lower than the national average (54 vs 59 nationally); females had slightly higher dietary quality than males and a higher mean fat avoidance score, although differences were not clinically significant. Intakes of carbohydrate, saturated fats, and cholesterol were higher than recommended daily allowances. Conclusions: The overall preference for speaking Spanish and the influence of language on dietary intake should inform future dietary interventions. Accommodating cultural norms and food preferences remain major challenges to improving dietary quality among the diverse Hispanic ethnic groups.